In-vitro bio- efficacy of Trichoderma against lentil wilt pathogen - PRIYANKA SINGH, SANJEEV KUMAR* and (Indian Phytopathology, 2016)
Three biocontrol agent viz., Trichoderma viride, T. harzianum and T. virens were evaluated to test the antagonism against Fusarium oxysporum f.sp. lentis under in vitro conditions All the three antagonists’ viz., Trichoderma viride, Trichoderma harzianum and Trichoderma virens have the potential of parasitizing the growth of Fusarium oxysporum f.sp. lentis in vitro. The rate of parasitism was fastest in T. viride (56.6% over growth in 96 hrs) then T. harzianum and T. virens in the present study. The volatile compounds from T. viride suppressed the mycelial growth of F. oxysporum f. sp.lentis by 58.7% and found effective when compared to others. Non-volatile compounds or culture filtrate from T. viride at 10% concentration shows complete mycelial inhibition of the test fungi. The antagonist T. viride was chosen to be the most promising bio-control agent for F. oxysporum f. sp. lentis.